The rusty plumage coloration of juvenile gyrfalcons is produced by pheomelanin and its expression is affected by an intracellular antioxidant - Galván, Ismael; Jorge, Alberto (Journal of Raptor Research, 2015)
Juveniles of many diurnal raptors exhibit a characteristic rusty plumage coloration whose biochemical basis has never been determined. Using the Gyrfalcon (Falco rusticolus) as a model species, we analyzed feathers by Raman spectroscopy and showed that the rusty color is due to the presence of the pigment pheomelanin, which was also observed in the feathers of a juvenile Peregrine Falcon (Falco peregrinus). We experimentally modified the expression of the rusty plumage coloration by treating four developing Gyrfalcons with buthionine sulfoximine (BSO), a specific and nontoxic inhibitor of glutathione (GSH) synthesis. Because cysteine, one of the three constitutive amino acids of GSH, is required for pheomelanin synthesis and GSH is the most important intracellular antioxidant, these findings indicate that the expression of rusty plumage coloration can be affected by environmental oxidative stress. Our results suggest that the rusty plumage coloration of at least some diurnal raptors is pheomelanin-based, and the dependence on GSH levels opens the possibility that the evolution of this trait in some species and the age-related variation in its expression across species may be explained by interspecific and intraspecific variation in exposure to environmental factors that generate oxidative stress and by age-related variations in endogenous levels of oxidative stress Peer reviewed